Gastroschisis: Antenatal Sonographic Predictors of Adverse Neonatal Outcome. (21st December 2014) - Page, Rachael; Ferraro, Zachary Michael; Moretti, Felipe; Fung Kee Fung, Karen
Abstract : Objectives . The aim of this review was to identify clinically significant ultrasound predictors of adverse neonatal outcome in fetal gastroschisis. Methods . A quasi-systematic review was conducted in PubMed and Ovid using the key terms "gastroschisis, " "predictors, " "outcome, " and "ultrasound." Results . A total of 18 papers were included. The most common sonographic predictors were intra-abdominal bowel dilatation (IABD), intrauterine growth restriction (IUGR), and bowel dilatation not otherwise specified (NOS). Three ultrasound markers were consistently found to be statistically insignificant with respect to predicting adverse outcome including abdominal circumference, stomach herniation and dilatation, and extra-abdominal bowel dilatation (EABD). Conclusions . Gastroschisis is associated with several comorbidities, yet there is much discrepancy in the literature regarding which specific ultrasound markers best predict adverse neonatal outcomes. Future research should include prospective trials with larger sample sizes and use well-defined and consistent definitions of the adverse outcomes investigated with consideration given to IABD.